ANALISIS PEMBERSIHAN KARAT PADA RING PLAT MENGGUNAKAN DRUM POLISHING MACHINE DENGAN MEDIA SOLAR - Haryanti, Nunung; Sofiyanto, Helmi Fikri; Bahtiar, Muhammad Dai; Ariyanto, Nur Aidi (Nozzle : Journal Mechanical Engineering, 2022)
The right tool to facilitate everyone's work is the desired tool, especially the features that can meet consumer needs. The tool must provide many advantages and advantages over existing tools in terms of performance and operational test results. One of its applications is tools for SMEs and the metal industry, such as cleaning metal rust, in the form of a drum polishing machine (DPM). In this study, a slightly different drum polishing machine that has been used by small businesses and large industries, namely adding a timer. This research is to analyze the results of the cleaning process using a drum polishing machine using diesel fuel as a cleaning medium with variations, namely, 100 ml, 125 ml, and 150 ml. The duration of the process is 2 hours. Every 30 minutes a specimen is taken to see the cleaning results. The variation that produces the best cleaning process is 150 ml diesel fuel.